Kebahagiaan dalam Utilitarianism John Stuart Mill - Renda, Fransiskus Xaverius (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2023)
This writing explores John Stuart Mill's view on happiness as the foundation of morality and the basic principle of moral actions within the framework of utilitarianism. Mill posits that general happiness, individual freedom, and the quality of happiness are key elements in his concept of happiness. However, this writing also critiques Mill's perspective by highlighting some dilemmas, such as the potential for hedonism in the quality of happiness, the need to deeply consider each action, and the applicability of this concept in a society with low moral consciousness. Additionally, through this writing, the author contrasts Mill's views with John Rawls' views on justice as fairness. Therefore, the author attempts to demonstrate their criticism of utilitarianism in achieving a concept of fair justice because of its focus on individual happiness rather than general happiness. Despite criticisms of utilitarianism and hedonism for lacking absolute moral commands, Mill establishes three major principles as guidelines for action, emphasizing the importance of individual freedom and justice in creating general happiness. This writing provides profound insights into the philosophical debate on morality, happiness, and justice, as well as their relevance to contemporary ethical dilemmas.ABSTRAKTulisan ini mengeksplorasi pandangan John Stuart Mill tentang kebahagiaan sebagai landasan moralitas dan prinsip dasar tindakan bermoral dalam kerangka utilitarianisme. Mill mengemukakan bahwa kebahagiaan umum, kebebasan individu, dan kualitas kebahagiaan merupakan elemen kunci dalam konsep kebahagiaannya. Namun, tulisan ini juga mengkritik pandangan Mill dengan menyoroti beberapa dilema, seperti potensi hedonisme dalam kualitas kebahagiaan, kebutuhan untuk mempertimbangkan setiap tindakan secara mendalam, dan aplikabilitas konsep ini dalam masyarakat dengan kesadaran moral yang rendah. Selain itu, melalui tulisannya ini penulis juga membandingkan pandangan Mill dengan John Rawls mengenai keadilan sebagai fairness. Karenanya, penulis berusaha menunjukkan kritiknya akan paham utilitaritas dalam mencapai konsep keadilan yang adil karena fokusnya pada kebahagiaan individu daripada kebahagiaan umum. Meskipun utilitarianisme dan hedonisme dikritik karena kurangnya perintah wajib mutlak, Mill menetapkan tiga prinsip besar sebagai pedoman bertindak, menekankan pentingnya kebebasan individu dan keadilan dalam menciptakan kebahagiaan umum. Tulisan ini memberikan wawasan mendalam tentang debat filosofis mengenai moralitas, kebahagiaan, dan keadilan, serta relevansinya dengan dilema etis kontemporer.